Papal Greed : The Theft of the Pala Monteluce and its Return to the Italian Peninsula - Beckers, Julie (2017)
This article examines the tortuous commission and subsequent loss of the famous Coronation of the Virgin by the Italian Master Raphael. It traces the naissance of the altarpiece (1503-25) as one of the key commissions by the Poor Clares of the convent of Santa Maria di Monteluce in Perugia, the looting of the piece by Napoleon’s invading troops in 1797 and, finally the stubborn Pope’s decision not to send the piece back to Perugia after the end of Napoleon’s reign, keeping it for his own growing Pinacoteca Vaticana, where the piece still rests today.